Zombie Credit and (Dis‐)Inflation: Evidence from Europe - ACHARYA, VIRAL V.; CROSIGNANI, MATTEO; EISERT, TIM; EUFINGER, CHRISTIAN (Journal of Finance, 2024)
ABSTRACT We show that “zombie credit”—subsidized credit to nonviable firms—has a disinflationary effect. By keeping these firms afloat, zombie credit creates excess aggregate supply, thereby putting downward pressure on prices. Granular European data on inflation, firms, and banks confirm this mechanism. Markets affected by a rise in zombie credit experience lower firm entry and exit, capacity utilization, markups, and inflation, as well as a misallocation of capital and labor, which results in lower productivity, investment, and value added. If weakly capitalized banks were recapitalized in 2009, inflation in Europe would have been up to 0.21 percentage points higher post‐2012.